Kepemimpinan: Usaha Pemberdayaan Pemimpin Baru Menuju Pertumbuhan Organisasi Berkelanjutan - Thomas Ulun Ismoyo (Humaniora, 2013)
“Leadership is the capacity and the willingness to rally men and women to a common purpose. But it also a character which inspires confidence.” These are the words uttered by Bernard Montgomery, a British Field Marshal, when asked what leadership meant to him. From his quote, he reveals the importance of the role of a leader in any organization. A leader will direct and at the same time emit confidence to his followers. In life, human beings are the main catalyst for the world’s living history. The same applies to any organization. Human is the most important agent that creates, develops and keeps the whole institution running smoothly. However not everyone is capable of leadership. One needs a competent characteristic and various qualifications to execute the role. The organization must first make an effort and sizeable attention to attract such personnel who can make a valuable contribution to the organization. One of the effort may be to establish a leadership development program. With the specific objective of producing more competent leaders, it needs special leader who can guide, influence, and develop people within the organization. Leadership development becomes a serious task for any organization because its fate and future lies on the capability of its new leaders. Leadership development in every organization is both personal and communal. Personal because there is an individual effort to progress and improve himself so that he will finally be trusted to lead in the organization. However this personal progression needs a support system and a structure that supports and facilitate every type of personality to become a dependable leader. This macro support system is communal in characteristic.